The Effect of Work Stress on Work Engagement with Burnout as a Mediating Variable for Health Workers During the COVID-19 Pandemic - Anna Partina; S Suparmono; Eka Sudarusman (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This study aimed to examine the effect of work stress on work engagement with burnout as a mediating variable. The phenomenon of work stress on medical personnel is a major concern during the COVID-19 pandemic. Work fatigue is very likely to occur due to the high workload and high work risk. The study was conducted on health workers in Yogyakarta using a purposive sampling technique so that a sample of 130 people was obtained, and the study was conducted during a pandemic. By using macro regression, the research results show that work stress does not affect work engagement (p = 0.415), work stress hurts burnout (p = 0.000), and burnout does not affect work engagement (p = 0.468). This study was also used to examine the role of burnout as a mediating variable. The results showed that burnout was not able to mediate the effect of work stress on work engagement.